Interactions in Virtual Customer Environments (VCEs) toward Customer Relationship Management (CRM): A Study of Tourist Hotels in Sri Lanka - Weerasinghe, Ishani; Warnakulasooriya, B.N.F. (International Review of Management and Marketing, 2019)
With the introduction of digitalization, Virtual Customer Environments (VCEs) play a significant role in the business world and it has become a strategic indicator for the success of business. Consequently, business entities have established VCEs, which enable customers and firms to virtually interact and build a relationship with each other. This study examines the impact of customer interactions in such VCEs on the nature of customer-business relationships of tourist hotels in Sri Lanka. The study is significant to Sri Lankan context as no studies have been conducted in this field. The study was developed and tested a conceptual model using a scientific quantitative research methodology. According to the results, it was found that customer interactions in VCEs associate the nature of customer-business relationships of the tourist hotels in Sri Lanka while virtual customer experience mediates the said association. Thus, VCEs should be an integral element of firms' CRM strategy in the context of the tourist hotels in Sri Lanka. Keywords: Virtual Customer Environments, Customer Interactions, Customer Experience, Customer-business relationships, Customer Relationships Management. JEL Classification: M31 DOI: https://doi.org/10.32479/irmm.7341